Amniotic fluid‐derived stem cell potential for therapeutic and surgical use: A review of the literature. (17th January 2022) - Baughn, Caroline; Campion, Stephani; Elbabaa, Samer
Abstract: Objective: Spina bifida is a debilitating neutral tube defect affecting many infants. The impact and severity of spina bifida depends on whether the patient exhibits a closed defect, spina bifida occulta, or an open defect, spina bifida aperta. Patients with spina bifida have physical and mental disabilities which merit further research into less invasive, more successful treatments. In addition to serving as protection for the growing fetus and facilitating nutrient exchange, amniotic fluid (AF) is a rich source of a mixed population of stem cells. As such, in vitro culture of AF‐derived stem cells has shown promise among therapeutic and surgical applications. We present a critical evaluation of the current preclinical efforts, amniotic fluid‐derived stem cell (AFSC) culture process, and the subsequent therapeutic application, with a focus on improvements for spina bifida outcomes in the pediatric patient population. Method: An evidence ‐ based literature review to investigate the current literature surrounding AFSC culture and use, with an emphasis on the benefits for spina bifida treatment. Results: 47 literature sources from PubMed and three studies from ClinicalTrials.gov. Conclusion: This review synthesizes the current literature, which shows promising data on AFSC pluripotency, as well as successful in utero coverage from AFSC ‐ supported environments in a multitude of animal models. Key points: What's already known about this topic? Amniotic fluid is a source of a mixed population of stem cells from which in vitro culture of amniotic fluid‐derived stem cells (AFSCs) provides promise among a variety of therapeutic and surgical applications. AFSCs have shown potential for treatment of neural tube defects, such as spina bifida. "Trans‐amniotic stem cell therapy" or TRASCET, specifically, has shown success in treatment of spina bifida animal models. What does this review add? We provide a stream‐lined overview of the current knowledge regarding AFSC surgical and therapeutic use, with an emphasis on the benefits for spina bifida outcomes in the pediatric patient population. In addition, we also identify specific and relevant gaps inhibiting further progression with AFSC use in clinical research and practice.